PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) : STUDI KASUS PADA PEMBELAJARAN IPAS PESERTA DIDIK KELAS V DI SD NEGERI 020 TANAH GROGOT - Muji Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of the Student Teams Achievement Division (STAD) learning model in the IPAS subject for Grade V students at SD Negeri 020 Tanah Grogot still faces several challenges. Therefore, the aim of this study is to investigate the cognitive learning outcomes in the IPAS subject for Grade V students at SD Negeri 020 Muara Koman. This study employs a qualitative research method with respondents consisting of teachers, students, and the school principal. Respondents were selected through purposive sampling based on the objectives of the research. Snowball sampling was also used through the involvement of participants recommended by initial respondents. The research procedure began with the researcher preparing instruments and instructional tools based on the Student Teams Achievement Division (STAD) learning model. The study was conducted using interview and observation techniques. Data analysis was carried out through both interim and final conclusions formed during the interview process. The results of the study indicate that the teacher respondent had prepared, implemented, and evaluated the implementation of the Student Teams Achievement Division (STAD) learning model in Grade V at SDN 020 Tanah Grogot. The student respondents had engaged in preparation, participated in the learning process, and demonstrated improved cognitive learning outcomes. Meanwhile, the school principal respondent had facilitated the preparation, implementation, and evaluation of the STAD learning model, resulting in enhanced cognitive learning outcomes among the students.